Law Enforcement On River Pollution Due To Batik Industry Waste In Simbang Kulon Sub-District, Buaran Regency, Pekalongan - Pramesti, Titis (UMPurwokerto Law Review, 2022)
Abstract One of the sites that became the hub of the batik business is Simbang Kulon Village, Buaran District, Pekalongan Regency. This industry has an impact since it produces solid waste in the form of wax and liquid waste in the form of bleach and batik cloth colors, both of which can pollute rivers because the garbage is released directly into them without being treated first. The study goal is to determine and analyze how efforts are made to enforce the law against river pollution due to batik industry waste in Simbang Kulon Village, Buaran District, Pekalongan Regency, based on Perda Pekalongan Regency Number 5 of 2014 concerning Wastewater Management, as well as to identify and analyze the factors that impede efforts to enforce the law against river pollution due to batik industry waste in Simbang Kulon Village, Buaran District, Pekalongan Regency. The normative juridical method, also known as the doctrinal method, is a process through which the law analyzes or investigates itself from the perspective of itself as a value system, a conceptual system, and a positive legal system. Keywords: Law enforcement, river pollution, and waste from the batik industry. Abstrak Kelurahan Simbang Kulon, Kecamatan Buaran, Kabupaten Pekalongan merupakan salah satu daerah yang menjadi sentra industri batik. Dampak dari industriÂ Â iniÂ Â menghasilkanÂ Â limbahÂ Â padat berupa lilinÂ danÂ limbahÂ cairÂ dariÂ obatÂ pemutihÂ maupun pewarnaÂ Â kainÂ Â batikÂ Â yangÂ Â dapatÂ Â menyebabkan pencemaranÂ Â Â karenaÂ limbahÂ Â Â tersebutÂ Â Â dibuang langsung ke sungai-sungai sekitar tanpa diolah terlebih dahulu. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisa bagaimana upaya dalam penegakkan hukum terhadap pencemaran sungai akibat limbah industri batik di Kelurahan Simbang Kulon, Kecamatan Buaran, Kabupaten Pekalongan berdasarkan Perda Kabupaten Pekalongan Nomor 5 Tahun 2014 tentang Pengelolaan Air Limbah serta mengetahui dan menganalisa faktor penghambat upaya penegakan hukum terhadap pencemaran sungai akibat limbah industri batik di Kelurahan Simbang Kulon, Kecamatan Buaran, Kabupaten Pekalongan. Metode yang digunakan dalam penelitian ini adalah metode yuridis normatif atau dikenal dengan metode doktrinal, yaitu hukum meninjau atau menilik dirinya dari sudut pandang dirinya sendiri sebagai sistem nilai, sebagai sistem konseptual dan sebagai sistem hukum positif. Kata kunci:Penegakkan Hukum, Pencemaran Sungai, Limbah Industri Batik.